IDENTIFIKASI NILAI ESENSIAL DARI OUTLIER NON-EXTREME MENGGUNAKAN METODE MINIMUM VOLUME ELLIPSOID - Risna Yuliani (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2023)
In many cases, outliers are considered to have a negative effect because they can cause the test to miss significant findings or distort the results in the data. Outliers are often discarded because they are considered an anomaly. Currently, some outliers carry essential information that cannot be discarded immediately. This study uses the Minimum Volume Ellipsoid estimator to treat the identified outliers differently. In this study, strong evidence was found that outliers do not have a completely negative connotation. Outliers should be treated differently because they carry essential information. This observation namely non-extreme outlier. The case study in this research uses house advertisement data from 5 districts in North Kalimantan and Berau district in East Kalimantan. The house in Tanjung Selor, Bulungan Regency, North Kalimantan, and Jalan Purnawirawan No. 21, RT 06, Karang Anyar, West Tarakan are suspected to be non-extreme outliers.